In vitro monitoring of glutathione via a switched-on effect based on a lanthanide incorporated carbon nanostructure with biocompatibility - Wen, Qin; Zeng, Zhi; Liu, Wanqiang; Gao, Jinwei; Zhang, Helen Meihua; Zhang, Cheng Cheng; Zheng, Yuhui (Synthetic metals, 2019)
•Carbon nanoparticles derived from 3-hydroxybenzoic acid were achieved.•Lanthanide was incorporated into the nanosystem.•An “off-on” change was discovered in the presence of GSH. Selective determination of targets in live cells and the real-time detection of active species will be highly valuable in biological field. Integration of 3-hydroxybenzoic acid and europium ions under hydrothermal conditions would lead to the formation of regular carbon nanoparticles with the size of 10–20 nm. This novel nanostructure possessed striking blue luminescence and no effective lanthanide signals were detected. In the presence of glutathione (GSH), the europium incorporated nanoparticles showed intensive red luminescence and an “off-on” change was observed. It has been accepted that GSH acts as an antioxidant to protect cell via entrapping free radicals and it controls oxidative stress within living systems. The abnormal levels of GSH will be closely related to a variety of diseases. Therefore, the bio-distribution and in vitro detection of GSH were investigated in this study. The biocompatibility and cytotoxicity of the europium incorporated nanoparticles were also evaluated by MTT assay and flow cytometry. This new system will be essential to monitor the concentration of important biological compounds in living organisms.